Sol-Gel Synthesis of Zinc Alumotitanate, Monitoring of Chelation, Hydrolysis, Condensation, and Crystallization Processes - Stanislav Kurajica; Vilko Mandić (Molecules, 2024)
Zinc alumotitanate sorbents with various compositions were prepared through sol-gel synthesis with the use of ethyl acetoacetate as a chelating agent. The formation and decomposition of chelates, providing insight into sol-gel process advancement, have been successfully monitored via 1H NMR, 13C NMR, and FTIR spectroscopy. It has been established that Al(OBus)3 and Ti(OBun)4 react completely with Eaa, forming chelates after 1 h, while after 24 h hydrolysis is already advanced. Hydrolysis is accelerated in the presence of Zn(NO2)3·6H2O, supplying the water needed for hydrolysis. In dried gels, the amount of ethyl acetoacetate is greatly reduced, and it is mainly present unbound. According to XRD analysis, samples with none or less titania are composed of layered double hydroxide, while in samples with greater amounts of titania, crystal nitrates are present. In all samples except those without Al, the spinel phase with variable composition crystallizes.